El capital humano y sus efectos sobre el crecimiento económico en Colombia (2010-2023): un análisis a partir de la educación superior (2025)
This study analyzes the effects of human capital on economic growth in Colombia during the period 2010-2023, with a particular emphasis on higher education. The main objective is to examine how university and postgraduate education impact key variables such as Gross Domestic Product (GDP), productivity and national competitiveness. To do so, a multiple linear regression econometric model with logarithmic transformations is used, which allows measuring the elasticities of GDP in relation to the employed population and educational levels. The results highlight that postgraduate education has the most significant impact on GDP, followed by university education and employment. The analysis reveals a constant increase in GDP and educational levels during the period studied.